PENERBITAN IZIN REKLAMASI TELUK BENOA BALI - Burhan Adlansyah; Sriwati; Nabillah Amir (CALYPTRA, 2021)
Abstract — Benoa Bay will be reclaimed when the Governor of Bali issues SK 2138/02-C / HK / 2012. Because the decree is considered to be in conflict with the prevailing laws and regulations and the publication does not involve the aspirations of the public. The Governor of Bali then issued Decree 1727/01-B / HK / 2013 which was the cancellation of the previous decree and gave permission to PT. TWBI to conduct a feasibility study then the government changed the allotment of the Benoa Bay which was once a conservation area (Zone L3) into a public use area (Zone P) with the issuance of Perpres 51/2014 Amendment to RTRKP SARBAGITA, in the Presidential Regulation requires that the Benoa Bay through revitalization activities can be held reclamation area of 700 Ha. The research method used is normative juridical. The results showed an indication of efforts to bleach spatial violations because the revision of the spatial plan was done not to whiten the deviation of the implementation of spatial use. And in the issuance of the Perpres the government does not involve the participation of the community, this is a form of the principle of openness in spatial planning and reclamation activities must have a location permit that is adjusted to the RZWP3K and RTRW. With its status in RZWP3K as a conservation area in the Badung Regency RTRW Regulation. So the reclamation permit cannot be granted and the existence of Benoa Bay must be maintained because the Balinese people agree that every development in Bali must be based on the values of local wisdom in the Tri Hita Karana concept. Keywords: presidential regulation, benoa bay, regional regulation, spatial planning, reclamation Abstrak— Teluk Benoa akan direklamasi ketika Gubernur Bali mengeluarkan SK 2138/02-C/HK/2012. Karena SK tersebut dianggap bertentangan dengan peraturan perundang-undangan yang berlaku dan dalam penerbitanya tidak melibatkan aspirasi masyarakat. Gubernur Bali kemudian mengeluarkan SK 1727/01-B/HK/2013 yang merupakan pembatalan SK sebelumnya dan memberikan izin kepada PT. TWBI untuk melakukan studi kelayakan kemudian pemerintah merubah peruntukan Teluk Benoa yang dulunya sebagai kawasan konservasi (Zona L3) menjadi kawasan pemanfaatan umum (Zona P) dengan diterbitkanya Perpres 51/2014 Perubahan Atas RTRKP SARBAGITA, dalam Perpres tersebut menghendaki Teluk Benoa melalui kegiatan revitalisasi dapat diselenggarakan reklamasi seluas 700 Ha. Metode penelitian yang digunakan adalah yuridis normatif. Hasil penelitian menunjukkan adanya indikasi upaya pemutihan pelanggaran tata ruang karena revisi terhadap rencana tata ruang dilakukan bukan untuk pemutihan terhadap penyimpangan pelaksanaan pemanfaatan ruang. Serta dalam penerbitan Perpres tersebut pemerintah tidak melibatkan peran serta masyarakat, hal ini sebagai bentuk prinsip keterbukaan dalam penataan ruang dan kegiatan reklamasi wajib memiliki izin lokasi yang disesuaikan dengan RZWP3K dan RTRW. Dengan statusnya dalam RZWP3K sebagai kawasan konservasi dalam Perda RTRW Kabupaten Badung. Maka izin reklamasi tidak dapat diberikan dan keberadaan Teluk Benoa harus dapat dipertahankan karena masyarakat Bali sepakat bahwa setiap pembangunan di Bali harus didasarkan pada nilai-nilai kearifan lokal dalam konsep Tri Hita Karana. Kata kunci: peraturan presiden, teluk benoa, peraturan daerah, penataan ruang, reklamasi